Physical limnology of large floodplain lakes along the lower Amazon river - Pétala Bianchi Augusto-Silva (2019)
Large, shallow lakes are common in the extensive floodplains throughout the tropics and its importance for climate regulation has already been proven. To determine controls on their mixing dynamics in order to help define proper simplifications to insert this type of lakes in land surface models, five stations were instrumented with meteorological and temperature sensors and placed in two shallow connected tropical lakes on the lower Amazon floodplain. A tight relation between changes in thermal structure and LMO/h (the ratio of the Monin- Obukhov length scale LMO to the depth of the actively mixing layer h) indicates the sensitivity of thermal structure to wind speed relative to heating and cooling. Four regimes led to variations in mixing: (i) high solar radiation with light winds in the mid-morning to early afternoon resulted in shallow stratification, 0 < LMO/h <1; (ii) afternoons with higher winds caused the diurnal thermocline to downwell and heat to mix to deeper layers, LMO/h >1; (iii) by late afternoon, buoyancy flux became negative and LMO/h < -1 and with W u and w both > 0.06 m.s-1, mixing from wind and cooling co-occurred; and (iv) convection dominated mixing on nights with light winds, -1 < LMO/h < 0. Pattern (ii) occurred mid-day if winds were higher. When winds were intermittent and regime (i) predominated mid-day, changes in heat content were primarily determined by one-dimensional processes of heating and cooling. When easterly winds were sustained and regime (ii) occurred mid-day, heat was transported west in the day, and colder water upwelled to the west or was advected to the west and north at night. Subtle differences in wind speed determined the extent to which advection moderated the thermal structure. Wind and solar radiation were found to be the most important parameters influencing the water column thermal structure of the lakes under study. Given the regimes identified by the in situ measurements and the increasingly applicability of orbital remote sensing to the study of the temperature patterns on inland aquatic systems, a model was developed for extracting bulk temperature (equivalent to that measured in situ) from the surface temperature (called skin temperature) provided by the MOD11A1 product of the MODIS sensor onboard the Aqua and Terra satellites. This model was calibrated and validated using a Monte Carlo simulation, resulting in a normalized error of 18.32%. The model, however, presented low R2 values, indicating that further research is needed on longer time series before this product can be used for pattern studies.